Technological characterisation of roofing slate from Nepal (Journal of Nepal Geological Society, 2016)
Roofing slate is a group of natural stones which can be split into thin, large and regular tiles. The world’s slate market is the third in importance for natural stone, just after granite and marble. Most of the world’s production of roofing slate is concentrated in Spain. There are new emerging countries (Brazil, China, India and Nepal) with huge resources of roofing slate. However, many of these resources are not yet well studied. Nepalese slate industry is still incipient, although most of the houses have been constructed using roofing slate since historic time. The representative three samples were taken for quality assessment from Tanahun and Baglung districts. From a geological point of view, the productive formations are the Benighat Slates and Nourpul Formation, but other formations are likely to be potential slate sources. Previous studies have shown an important reserve of slate which needs detailed investigation. Petrography and mineralogy of representative Nepalese slates are similar to the rest of the world’s roofing slate. The test results showed values within the acceptance thresholds for roofing slates. This paper also compares the Nepalese slates with other varieties of roofing slates from Spain. Roofing slate industry of Nepal is promising, but still there are many points to improve.